Flight of a Guided Aerial Bomb Along a Vertical Plane in Turbulent Atmosphere - Konrad STEFAŃSKI; Marta GRZYB (Problemy Mechatroniki)
The control of a homing flying object, which a guided aerial bomb (GAB) is, takes place in the earth’s atmosphere, which may feature various atmospheric phenomena that are disturbances to the GAB control. The atmospheric disturbances include air turbulences, wind pockets, and wind gusts. For the purpose of the research discussed in this paper, the atmospheric disturbances were qualified as a stochastic process of power spectral density according to the Dryden model. This paper presents a method of controlling a GAB in motion through a turbulent atmosphere of the earth. The GAB was homed to a moving ground target by the most universal method of proportional navigation. The research discussed in this paper included an analysis of the effect of atmospheric disturbances on the target striking accuracy of a GAB moving along a vertical plane, the GAB flight trajectory, the values of force inputs which controlled the GAB flight, the values of actual attack angles, the values of kinematic transverse overloads, and the control errors input to the guidance controller. The numerical simulations were completed during the research in Matlab/Simulink, and certain results thereof are represented in a graphical format.